Chronic Kidney Diseases and Acute Kidney Injury in Patients With COVID-19: Evidence From a Meta-Analysis - Zhou, Yangzhong; Ren, Qidong; Chen, Gang; Jin, Qiao; Cui, Quexuan; Luo, Huiting; Zheng, Ke; Qin, Yan; Li, Xuemei (Frontiers in Medicine, 2020)
Renal involvement has been implicated in COVID-19, but the related prevalence and prognosis were largely unknown. In this meta-analysis, we searched literature from PubMed, Embase, through bioRxiv, and medRxiv until April 26, 2020. Studies reporting chronic kidney diseases (CKD) and/or acute kidney injury (AKI) were included. Demographics, relevant data of disease severity, and patient’s prognosis were extracted and aggregated. 21164 patients from 52 peer-reviewed studies were included. 37 studies (n=16922) reported CKD in COVID-19 patients at diagnosis, and the pooled prevalence was 3.52% (95% CI 1.98–5.48%; I²=93%). Subgroup analysis showed that CKD prevalence was higher in severe cases (odds ratio OR 3.42, 95% CI 2.05-5.61; I²=0%) compared to those with non-severe disease, and deceased cases (6.46, 3.40–12.29; I²=1%) compared with survivors. Pooled prevalence of CKD was lower in Chinese patients (2.56%, 95% CI 1.79-3.47%; I²=80%), compared to those outside of China (6.32%, 95% CI 0.9-16.12%; I²=93%) (p=0.08). The summary estimates for AKI prevalence was 11.46% (95%CI 6.93-16.94%). Patients with AKI had a higher prevalence of developing into severe cases (OR 6.97, 95% CI 3.53-13.75; I²=0%) and mortality risk (45.79, 36.88-56.85; I²=17%). The prevalence estimates of CKD or AKI were not significantly different from preprint publications (p>0.05). Our study indicates that renal condition, either in CKD or AKI, is associated with COVID-19 prognosis, and taking care of such patients need further awareness and investigations.